Assessment of influence of input method of modifying additive in the coating of electrode on their welding-technological properties and mechanical properties of the weld metal - N. I. Urbanovich; T. I. Bendik; K. E. Baranovsky; E. V. Rozenberg (Литьë и металлургия)
A comparative analysis and assessment of the impact of the method of introducing the modifying additive in the form of dispersed and ultrafine particles into the electrode coating on their welding-technological properties and mechanical properties of the weld metal is carried out. It has been established that a modifying additive containing such chemical elements as barium, strontium, potassium, silicon, aluminum, vanadium is a mixture of stable alkaline-earth metal compounds in the form of carbonates and is inserted into the coating of the electrodes by applying its dry mixture into the composition prior to their crimping, allows to improve the welding-technological characteristics of the electrode and grind the structure of the weld metal, which contributes to the improvement of its mechanical properties particularly ductility.